Science and technology in the twenty-first century - Herschbach, Elisabeth (Defining events of the twenty-first century., 2020)
Explores scientific breakthroughs and technological advances that have been made in the early part of the twenty-first century including smartphones, smart homes, bionic limbs, and robots. Includes fact boxes, source notes, and a list of websites for further information.